An interface modification method of an all-solid-state battery, a modified positive electrode material, a modified sulfide solid electrolyte, and an all-solid-state battery
Patent Information
- Application Number
- CN202611090021.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-20
AI Technical Summary
[0004]第二,空气稳定性差
[0019]1、正极、电解质双界面协同保护。本发明突破传统单一界面改性的技术局限,创新性地对正极和电解质颗粒同步实施纳米涂层包覆。在复合正极内部,包覆后的正极颗粒和电解质颗粒相互接触时,表面LiAlF4涂层之间可形成稳定的“层-层”耦合防护结构,彻底消除裸露的高活性界面,从根源上抑制硫化物电解质在高压下的氧化分解反应,大幅降低电池界面阻抗,改善电池循环衰减问题。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage battery technology, specifically relating to all-solid-state batteries, and more specifically to an interface modification method for all-solid-state batteries, particularly a modification method for simultaneously constructing a nano-coating on the surface of a cathode material and sulfide solid electrolyte particles, as well as electrodes, electrolytes and all-solid-state batteries prepared based on this method. Background Technology
[0002] All-solid-state batteries are considered an important development direction for next-generation energy storage devices due to their high safety and potential high energy density. Sulfide solid electrolytes (such as Li6PS5Cl, Li...) 5.5 PS 4.5 Cl 1.5 Due to their high ionic conductivity comparable to liquid electrolytes and good machinability, solid-state batteries have become a key research focus in the field of all-solid-state batteries.
[0003] However, existing sulfide solid electrolytes face two major technical bottlenecks in practical applications, which severely restrict the industrial application of sulfide-based all-solid-state batteries: First, the electrochemical window is narrow. Sulfide electrolytes are highly susceptible to oxidative decomposition on the high-voltage cathode side (such as LiCoO2, NCM). When in contact with high-voltage cathode materials, the electrolyte undergoes irreversible oxidation when charged to a high potential (>4.0 V), generating high-resistivity decomposition products (such as P2Sx, LiCl, elemental S), leading to a sharp increase in interfacial impedance and rapid capacity decay. Simultaneously, reductive decomposition also occurs when in contact with lithium metal on the anode side.
[0004] Second, it has poor air stability. Sulfide electrolytes readily react with water vapor to generate toxic H2S gas, which also damages their own structure and causes a sharp decline in ionic conductivity. This places stringent requirements on ultra-low humidity environments for battery preparation, assembly, and storage, significantly increasing production costs and process complexity.
[0005] To address the aforementioned issues, existing technologies have proposed methods such as coating the surface of the cathode material with inert oxides (e.g., LiNbO3, Li2ZrF6) or coating the surface of electrolyte particles with organic matter. However, these methods mostly focus on one-sided modification (modifying only the cathode or only the electrolyte). In practical composite cathodes, there are numerous solid-solid contact interfaces between the cathode active material, the sulfide electrolyte, and the conductive carbon, and one-sided modification cannot completely isolate all harmful contacts. Furthermore, traditional ball milling coating methods severely damage the brittle crystal structure of the sulfide electrolyte, significantly reducing its intrinsic ionic conductivity.
[0006] Therefore, developing an interface engineering strategy that is gentle on the process, causes no structural damage, and can effectively protect both the cathode and the electrolyte is crucial for promoting the commercialization of sulfide all-solid-state batteries. Summary of the Invention
[0007] To address the shortcomings of the existing technologies, this invention provides a dual-interface modification method for the cathode material and sulfide solid electrolyte of an all-solid-state battery electrode. This method utilizes vapor deposition to simultaneously construct an amorphous LiAlF4 nanocoating on the surfaces of both cathode material particles and sulfide solid electrolyte particles, thereby creating a three-dimensional physical isolation network within the composite cathode. This network simultaneously suppresses electrochemical decomposition and enhances air stability.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for modifying the interface of an all-solid-state battery includes the following steps: Step 1: Preparation of Precursor Raw Materials for Coating The invention provides positive electrode active material powder and sulfide solid electrolyte powder. The positive electrode active material is selected from layered oxides (such as LiCoO2, NCM), spinel, or olivine structural materials; the sulfide solid electrolyte is preferably Li6PS5Cl or Li having a sulfogermanium sulfide structure. 5.5 PS 4.5 Cl 1.5 .
[0009] Step 2: Vapor Deposition Coating The positive electrode active material powder and sulfide solid electrolyte powder prepared in step one were placed in a fluidized bed dispersion device. Using physical vapor deposition (PVD), a mixture of LiF and AlF3 (molar ratio 1:1) was used as the evaporation source. Electron beam evaporation was performed under vacuum conditions, causing the evaporated LiAlF4 material to be deposited on the particle surfaces of both powders, forming LiAlF4 nano-coatings of controllable thickness on the surfaces of the positive electrode particles and the sulfide electrolyte particles.
[0010] Step 3: Post-processing The powder that has been coated by vapor deposition is placed in an inert atmosphere for cooling treatment. The modified powder is then collected and can be directly used for the assembly of all-solid-state batteries.
[0011] Furthermore, the physical vapor deposition method is an electron beam evaporation method, and its process parameters are: vacuum degree below 3×10⁻⁶. -2 Pa, the electron gun accelerating voltage is 8-10 kV, and the current is 20-40 mA.
[0012] Furthermore, to precisely control the coating thickness and ensure uniformity, a "cyclic deposition" mode is adopted, that is, the coating thickness is precisely adjusted by controlling the number of depositions (1 to 5 times). Preferably, the thickness of the LiAlF4 coating formed by a single deposition is 2 to 10 nm, and the total coating thickness is controlled between 4 and 30 nm.
[0013] Furthermore, to achieve simultaneous modification of cathode material powder and sulfide electrolyte powder, batch processing or a dual-station fluidized bed device can be used. The cathode powder (e.g., LiCoO2) and electrolyte powder (e.g., Li...) are then processed. 5.5 PS 4.5 Cl 1.5 The two powders are placed in different fluidized bed containers and share a common electron beam evaporation source, which can achieve simultaneous or stepwise coating of the two types of powders.
[0014] A modified cathode material prepared by the above method, wherein the surface of the modified cathode material particles is coated with an amorphous LiAlF4 layer with a thickness of 2 to 20 nm.
[0015] A modified sulfide solid electrolyte prepared by the above method is disclosed, wherein the surface of the modified sulfide solid electrolyte particles is coated with an amorphous LiAlF4 layer with a thickness of 2–20 nm. Compared with the uncoated original electrolyte, the modified sulfide solid electrolyte shows no significant shift or increase / decrease in XRD characteristic peaks, indicating that the modification process does not destroy the bulk crystal structure of the electrolyte and that the structural integrity is excellent. After exposure to humid air with a dew point of -40°C to -30°C, its ionic conductivity retention rate is increased by more than 50% compared with the original electrolyte, significantly improving the air stability of the sulfide electrolyte.
[0016] An all-solid-state battery comprising the modified positive electrode material described above, the modified sulfide solid electrolyte described above, and a negative electrode, wherein the negative electrode is any one of lithium metal, lithium indium alloy, or graphite.
[0017] Furthermore, the composite cathode layer of the all-solid-state battery simultaneously incorporates the modified cathode material particles, the modified sulfide solid electrolyte particles, and conductive carbon. The LiAlF4 coating covering the surfaces of the cathode material particles and electrolyte particles effectively isolates the cathode / electrolyte / carbon three-phase interface, suppresses interfacial oxidation and decomposition side reactions under high-voltage conditions, and prevents the problem of continuously increasing interfacial impedance.
[0018] Furthermore, when the all-solid-state battery operates in a voltage range of 3.0 to 4.5 V (vs. Li / Li+), the coulombic efficiency of the first cycle can reach more than 85%, and the optimal efficiency can reach 90%. After 500 cycles at a 0.5C rate, the battery capacity retention rate is higher than 85%, demonstrating excellent cycle life and electrochemical stability. Beneficial effects
[0019] 1. Synergistic Protection of Cathode and Electrolyte Interfaces. This invention overcomes the limitations of traditional single-interface modification by innovatively applying a nano-coating to both cathode and electrolyte particles simultaneously. Inside the composite cathode, when the coated cathode and electrolyte particles come into contact, a stable layer-to-layer coupling protective structure forms between the surface LiAlF4 coatings. This completely eliminates the exposed highly active interface, fundamentally inhibiting the oxidative decomposition of sulfide electrolytes under high pressure, significantly reducing battery interface impedance, and improving battery cycle degradation.
[0020] 2. A non-destructive coating process is employed to maximize the preservation of the electrolyte's intrinsic high ionic conductivity. The fluidized bed coupled electron beam evaporation technology used in this invention is a dry vapor deposition method, distinct from traditional mechanical coating methods such as high-energy ball milling. The entire process is free from high-intensity mechanical impact and extrusion, effectively preventing damage to the sulfide electrolyte's crystal structure from external forces. This maximizes the preservation of the sulfide electrolyte's high intrinsic ionic conductivity of several mS / cm, fully leveraging the core performance advantage of the sulfide electrolyte's high conductivity and ensuring the excellent dynamic performance of the all-solid-state battery.
[0021] 3. The modified coating material exhibits excellent performance, combining electrochemical and environmental stability. The LiAlF4 material selected in this invention possesses an extremely wide electrochemical window (2.3–5.4 V), adaptable to the operating voltage range of high-voltage cathodes, and demonstrates good chemical stability under high-voltage conditions. Simultaneously, LiAlF4 material possesses excellent electronic insulation properties, effectively blocking the leakage and migration of electrons from conductive carbon or the cathode to the electrolyte interface, effectively preventing the continuous decomposition and failure of the electrolyte caused by "electron penetration." Furthermore, the inherent hydrophobic properties of fluorides significantly improve the air tolerance of sulfide electrolytes, effectively suppressing the reaction with moisture in the air to generate hydrogen sulfide gas and preventing structural collapse, thus greatly reducing the stringent environmental requirements for battery preparation, assembly, and storage.
[0022] 4. The process is green and efficient, with promising prospects for industrialization. The method of this invention is a completely dry process, using no solvents and producing no waste gas or wastewater. Electron beam evaporation combined with fluidized bed technology facilitates continuous and large-scale production and has good compatibility with existing roll-to-roll electrode fabrication processes. Attached Figure Description
[0023] Figure 1 The image shows the XRD pattern of the LiAlF4 thin film prepared in Example 1 of this invention.
[0024] Figure 2 The images show TEM images and EDS elemental distribution diagrams of the modified LiCoO2 (LCO-C3) of Example 1 of this invention.
[0025] Figure 3Modified Li in Example 1 of the present invention 5.5 PS 4.5 Cl 1.5 TEM image and EDS elemental distribution map of (LiPSCl-E3).
[0026] Figure 4 This is a high-resolution TEM image of modified LiCoO2 (LCO-C3) in Example 1 of the present invention.
[0027] Figure 5 This is a comparison chart of the first charge-discharge curves of the all-solid-state batteries of Example 1 (double-sided coating, LCO-C3+E3) and Comparative Example 1 (uncoated), Comparative Example 2 (positive electrode coating) and Comparative Example 3 (electrolyte coating) of the present invention.
[0028] Figure 6 This is a comparison chart of the long-cycle performance of the all-solid-state battery of Example 1 and Comparative Example 1 at a 0.5C rate.
[0029] Figure 7 The all-solid-state battery of Example 1 and Comparative Example 1 of this invention has a high areal loading (26.9 mg / cm³). 2 Comparison of cyclic performance under ( ). Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in detail below with reference to specific embodiments and accompanying drawings. However, the scope of protection of this invention is not limited thereto. Example
[0031] 1. Material Preparation Cathode material coating modification: 3.0 g of LiCoO2 (LCO) powder with a particle size D50 of 5.5 μm was weighed and placed in a fluidized bed dispersion device. Using a mixture of LiF and AlF3 (molar ratio 1:1) as the evaporation source, deposition was carried out under a vacuum environment of less than 0.03 Pa, with an accelerating voltage of 8.1 kV and a working current of 30 mA, via electron beam evaporation. The deposition process was repeated three times to obtain a modified LCO sample coated with a LiAlF4 nanocoating, denoted as LCO-C3.
[0032] Electrolyte material coating modification: Weigh 3.0 g Li 5.5 PS 4.5 Cl 1.5 LiPSCl powder with a particle size of approximately 1 μm was subjected to electron beam evaporation deposition using the same process parameters as described above. After three cycles of deposition, a modified LiPSCl sample coated with a LiAlF4 nanocoating was obtained, denoted as LiPSCl-E3.
[0033] 2. Material structure and morphology characterization results The modified samples prepared in this embodiment were characterized in terms of microstructure and composition. The specific results are as follows: like Figure 1 XRD confirmed that the LiAlF4 coating prepared by this process is amorphous.
[0034] like Figure 2 and Figure 3 TEM and EDS elemental distribution tests showed that Al and F elements were uniformly distributed on the surface of LCO and LiPSCl electrolyte particles, proving that a continuous and complete LiAlF4 coating was formed on the surface of the two types of powder particles.
[0035] like Figure 4 HRTEM test results show that the LCO surface coating has a uniform thickness of about 6 nm, and the coating effect is excellent.
[0036] 3. Assembly and testing of all-solid-state batteries Composite cathode preparation: Modified cathode material LCO-C3, modified sulfide electrolyte LiPSCl-E3 and vapor-grown carbon fiber (VGCF) were uniformly mixed in a mass ratio of 70:28:2 and placed in a vibratory ball mill, and ball milled at a frequency of 15 Hz for 20 min.
[0037] Battery Assembly: Battery assembly was performed in an argon-filled glove box. First, 150 mg of LiPSCl-E3 electrolyte powder was weighed and pressed into an electrolyte sheet at 280 MPa. The composite positive electrode powder was then evenly spread on one side of the electrolyte sheet and pressed again at 500 MPa. A lithium metal sheet or lithium-indium alloy foil was then bonded to the other side as the negative electrode, completing the all-solid-state battery assembly. When using lithium metal as the negative electrode, the stacking pressure was approximately 13 MPa; when using a lithium-indium alloy negative electrode, the stacking pressure was approximately 100 MPa.
[0038] Electrochemical testing: The assembled battery was subjected to electrochemical tests within a voltage window of 3.0–4.5 V (vs. Li / Li+). The test results are as follows: First charge and discharge test, such as Figure 5 The all-solid-state battery prepared by this invention has a first-cycle charging capacity of 207.1 mAh / g, a discharge capacity of 187.8 mAh / g, and a first-cycle coulombic efficiency as high as 90.2%.
[0039] Long loop tests, such as Figure 6 The all-solid-state battery using lithium indium alloy anode maintains a discharge capacity of 142.5 mAh / g after 500 cycles at 0.5C, with a capacity retention of 86.4% and an average coulombic efficiency of 99.92%, demonstrating excellent cycle stability.
[0040] High surface load test, such as Figure 7 When the LCO surface loading is as high as 26.9 mg / cm³ 2 At that time, the battery's first discharge capacity reached 4.3 mAh / cm². 2 It can stably cycle for more than 300 times.
[0041] Comparative Example 1 (Uncovered) In this embodiment, untreated raw LCO and raw LiPSCl were used to prepare a composite cathode and assemble an all-solid-state battery according to the same raw material ratio, ductile iron process, pressing parameters and assembly process as in Example 1. The test conditions were kept completely consistent with those in Example 1 to verify the technical advantages of the modification strategy of this invention.
[0042] refer to Figure 5 Electrochemical test results show that the unmodified all-solid-state battery in this embodiment has a first-cycle charging capacity of 170.7 mAh / g and a discharge capacity of only 137.1 mAh / g, with a first-cycle coulombic efficiency of only 80.3%.
[0043] refer to Figure 6 The long-cycle test results show that the capacity of the unmodified all-solid-state battery in this embodiment is only 85.8 mAh / g after 500 cycles at 0.5C rate, and the capacity retention rate is significantly lower than that of Example 1, indicating poor cycle stability.
[0044] refer to Figure 7 High load capacity tests show that the unmodified all-solid-state battery in this embodiment has a first-cycle discharge capacity of only 2.4 mAh / cm2, and the capacity decays rapidly during cycling, making it impossible to achieve stable long-term cycling and exhibiting poor high-load adaptability.
[0045] Comparative Example 2 (positive electrode only) Only the cathode material is coated with LiAlF4, while the sulfide electrolyte uses uncoated raw LiPSCl.
[0046] Material preparation: LCO-C3 cathode material was prepared three times using the same process parameters as LCO-C3 in Example 1. Untreated raw LiPSCl powder was used as the sulfide electrolyte.
[0047] Composite cathode preparation and battery assembly: A composite cathode was prepared by mixing LCO-C3, original LiPSCl electrolyte powder, and VGCF conductive agent at a mass ratio of 70:28:2. Original LiPSCl powder was used as the electrolyte layer, and lithium indium alloy was selected as the negative electrode. The remaining spherical graphite, pressing, and assembly steps were the same as in Example 1, and an all-solid-state battery with only one side of the positive electrode was obtained.
[0048] Electrochemical testing: like Figure 5 As shown, the first charge-discharge test results show that the first charge capacity of the single-sided positive electrode coated battery prepared in this embodiment is 189.2 mAh / g, the first discharge capacity is 161.8 mAh / g, and the first coulombic efficiency is about 85.5%.
[0049] like Figure 6 As shown, the long-cycle test results show that the single-sided positive electrode coated battery prepared in this embodiment retains a capacity of about 72.5% after 500 cycles at 0.5C rate. The cycle stability is improved compared with the uncoated comparative example 1, but it is still inferior to the double-sided coated modified system of example 1.
[0050] Air stability: Since the electrolyte is not covered with a protective coating, the original electrolyte is still prone to reacting with moisture in the air. After exposure to humid air, the battery performance still shows a significant decline. The inherent defect of poor environmental stability of this sulfide electrolyte has not been improved.
[0051] Comparative Example 3 (electrolyte coating only) Only the sulfide electrolyte is coated with LiAlF4, while the cathode material uses uncoated raw LCO.
[0052] Material preparation: LiPSCl-E3 electrolyte powder coated three times was prepared using the exact same process parameters as LiPSCl-E3 in Example 1. Untreated raw LCO powder was used as the cathode material.
[0053] Composite cathode preparation and battery assembly: The original LCO, LiPSCl-E3 electrolyte powder and VGCF conductive agent were mixed at a mass ratio of 70:28:2 to prepare a composite cathode. The electrolyte layer was LiPSCl-E3 powder, and the negative electrode was lithium indium alloy. The remaining spherical graphite, pressing and assembly steps were the same as in Example 1, and a solid-state battery with only the electrolyte on one side was obtained.
[0054] Electrochemical testing: like Figure 5 The initial charge-discharge test results showed that the first charge capacity of the single-sided electrolyte-coated battery was 197.5 mAh / g, the discharge capacity was 174.4 mAh / g, and the first coulombic efficiency was approximately 88.3%.
[0055] like Figure 6 Long-cycle test results show that after 500 cycles at 0.5C, the capacity retention rate of the single-electrolyte-coated battery is about 78.9%, which is better than Comparative Example 1, but slightly lower than Example 1, indicating that protecting the electrolyte alone cannot completely suppress the direct side reaction on the positive electrode side.
[0056] Table 1. Summary of Performance of Examples and Comparative Examples Comparative Example 1 None / None 80.30% 61.5% 0.95 (Pure LiPSCl) Comparative Example 2 Three layers / None 85.50% 72.5% - Comparative Example 3 None / Three-layer 88.30% 78.9% - Example 1 Three-story / Three-story 90.20% 86.40% 1.45 (LiPSCl-E3)
[0057] The raw LiPSCl and the LiPSCl-E3 powder prepared in Example 1 were exposed to air at a relative humidity of 1.55% (dew point -30°C) for 5 hours. Their ionic conductivity was then measured.
[0058] The conductivity of the original LiPSCl decreased sharply from approximately 3.0 mS / cm to 0.95 mS / cm.
[0059] The conductivity of LiPSCl-E3 remained at 1.45 mS / cm, proving that the LiAlF4 coating can effectively protect the sulfide electrolyte from moisture erosion.
[0060] In summary, the dual-interface nanocoating strategy proposed in this invention, through fluidized bed electron beam evaporation technology, simultaneously constructs an amorphous LiAlF4 layer on the surface of both the cathode and sulfide electrolyte particles, successfully solving the two core challenges of poor high-voltage stability and air sensitivity in sulfide all-solid-state batteries. This achieves a comprehensive performance breakthrough in high initial efficiency, long cycle life, high areal loading, and air stability, demonstrating enormous application potential.
[0061] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for interface modification of an all-solid-state battery, characterized in that, include: Obtain positive electrode active material powder and sulfide solid electrolyte powder; Amorphous LiAlF4 nanocoatings were deposited on the particle surfaces of the positive electrode active material powder and the sulfide solid electrolyte powder using physical vapor deposition to prepare the modified positive electrode material and the modified sulfide solid electrolyte.
2. The interface modification method according to claim 1, characterized in that, The physical vapor deposition method is electron beam evaporation. The evaporation source is a mixture of LiF and AlF3 in a molar ratio of 1:1; The vacuum level during the deposition process is less than 3 × 10⁻⁶. -2 Pa.
3. The interface modification method according to claim 1, characterized in that, The positive electrode active material is LiCoO2, NCM ternary material, LiNiO2 or LiMn2O4; The sulfide solid electrolyte is Li6PS5Cl or Li having a sulforaphite-germanium ore structure. 5.5 PS 4.5 Cl 1.5 .
4. The interface modification method according to claim 1, characterized in that, The thickness of the LiAlF4 coating can be controlled by controlling the number of depositions. The total thickness of the LiAlF4 nanocoating is 2–30 nm.
5. The interface modification method according to claim 3, characterized in that, The total thickness of the LiAlF4 nanocoating is 4–15 nm.
6. The interface modification method according to claim 1, characterized in that, During the deposition process, the positive electrode active material powder and the sulfide solid electrolyte powder are placed in separate fluidized dispersion devices to dynamically disperse and uniformly coat the powder.
7. A modified cathode material, characterized in that, Prepared by the interface modification method according to any one of claims 1-4 The modified cathode material is coated with an amorphous LiAlF4 nano-coating with a thickness of 2–20 nm.
8. A modified sulfide solid electrolyte, characterized in that, Prepared by the interface modification method according to any one of claims 1-4 The modified sulfide solid electrolyte is coated with an amorphous LiAlF4 nano-coating with a thickness of 2–20 nm. Furthermore, the modified sulfide solid electrolyte retains more than 50% of its ionic conductivity after being exposed to air with a relative humidity of 1.55% for no less than 5 hours.
9. An all-solid-state battery, characterized in that, It comprises the modified positive electrode material as described in claim 7, the modified sulfide solid electrolyte as described in claim 8, and a negative electrode.
10. The all-solid-state battery according to claim 9, characterized in that, The composite cathode layer of the all-solid-state battery comprises: the modified cathode material as described in claim 7, the modified sulfide solid electrolyte, and conductive carbon.
11. The all-solid-state battery according to claim 9, characterized in that, Within a voltage range of 3.0 to 4.5 V, the initial coulombic efficiency of the all-solid-state battery is not less than 85%, and the capacity retention rate after 500 cycles at a 0.5C rate is not less than 80%.